Analysis of the Implementation of the Radiation Occupational Safety and Health Management System (SMK3) in the Radiology Installation of Bhayangkara Hospital Semarang - Suraningsih, Nanik; Rosidah, Siti; Jamil, Masfufatun (Jurnal EduHealth, 2025)
Indonesian Government Regulation Number 63 of 2000 concerning safety and health in the use of ionizing radiation explains that the Radiation Safety Management System (SMKR) which must be applied in the use of radioactive substances or other radiation sources has 7 components, namely: (1) radiation protection organization, (2) radiation dose monitoring and radioactivity monitoring, (3) radiation protection equipment, (4) health checks, (5) document storage, (6) quality assurance and (7) education and training. This study aims to describe, understand, and analyze the implementation of the Radiation Occupational Safety and Health Management System (SMK3) in the Radiology Installation of Bhayangkara Hospital. The specific objective is to provide suggestions for improving the implementation of the radiation occupational safety and health management system (SMK3) in the Radiology Installation of Bhayangkara Hospital Semarang. The research method is descriptive qualitative. The subjects in this study were 5 radiographers and 1 head of the room. Data collection was carried out through observation, documentation, and interviews with radiographers and radiation protection officers. Data validity was carried out using triangulation techniques, namely triangulation of sources and data. Source triangulation is carried out by checking data obtained from several sources. Data processing is carried out through data reduction, data presentation, then data analysis with references and literature to draw conclusions and suggestions. The results of the research on radiation protection organizations, radiation dose monitoring, health checks, document storage, and quality assurance are good and well structured. Document storage is still manual. Education and training for radiation workers are planned at the beginning of each budget year and have limited budgets. Documentation suggestions are changed to digital form.